COBIT 2019 for Enhanced ICT Governance: A Case Study at a Higher Education Institution - Fitriyani, Baiq Yulia; Muhammad, Alva Hendi (Universitas Bina Darma, 2025)
Effective ICT governance is essential for aligning technological resources with institutional objectives, especially in higher education institutions with limited resources. This study evaluates the ICT governance framework at PUSTIK STMIK Lombok using COBIT 2019, focusing on six domains: APO04, APO10, BAI02, DSS01, DSS05, and EDM01. A structured survey was conducted with 189 respondents, including faculty, students, and administrative staff, to assess capability maturity levels and identify governance gaps. The results indicate that all domains achieved Level 3 (Established), reflecting standardized processes but highlighting deficiencies in security resilience, vendor management, and operational change management. A SWOT analysis identified weaknesses such as limited proactive security measures, insufficient stakeholder engagement, and inadequate staff training, while opportunities include government funding and emerging technologies. To address these challenges, a tailored governance framework was developed, incorporating policies, standards, and procedures to enhance security, innovation management, and vendor accountability. The findings underscore the applicability of COBIT 2019 in resource-constrained educational settings and provide practical recommendations to bridge governance gaps. Future research should examine the long-term effects of governance improvements and explore the framework’s scalability across similar institutions.